Crude Oil Pipeline Scale Deposition: Causes and Removal Methods - E. Eltaib, Omer.; A. Rabah, Ali (University of Khartoum Engineering Journal, 2022)
This work investigated the causes of scale formation and removal methods on 107 km crude oil pipeline of Diffra oil field of Muglad basin as a case study. The study is based on well and pipeline historical data of three years (2007, 2008 and 2009). The data included production data (net oil and water cut), choke opening, pipeline pressures, water qualities and scale composition. The study revealed that the main cause of scale formation is the presence of Ca+2 and Mg+2 in produced water and wax in oil. The scale consists of 78 % Ca+2, 12 % Mg+2 and 10 % wax. Investigations on removal methods revealed that the currently employed chemical removal method is effective; however the downtime (well shut down) is high making significant production cut. A method to reduce the cleaning down time is proposed. The pipeline is divided into two sections: aboveground and underground. The aboveground line is characterized with the presence of valves, choke and pipe reductions (i.e. non uniform cross section). The underground section is uniform in cross sectional area. For the aboveground section the current practice of chemical cleaning is recommended to be maintained however, with provision of a bypass line. For underground section the standard practice of pigging is recommended. The proposed cleaning method of the whole pipeline eliminates the downtime completely. In addition it is uncomplicated, with economical operation and installation cost. The method also make significant cut in chemical used hence reduces the hazard and environmental impacts.